1991
DOI: 10.1002/bit.260380514
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of microbial growth and metabolism by excess turbulence

Abstract: Excess turbulence caused by high-intensity stirring inhibited microbial growth and metabolism. In stirred tank bioreactors, the growth rate and lysine biosynthesis decreased in Brevibacterium flavum beyond 900 rpm, the growth rate of Trichoderma reesei on wheat straw beyond 150 rpm, and the growth rate of Saccharomyces cerevisae beyond 800 rprn. The term turbohypobiosis was introduced to describe this inhibition. Turbohypobiosis was characterized by a stress factor Fstr, expressing the interaction of medium fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(32 citation statements)
references
References 6 publications
1
31
0
Order By: Relevance
“…However, even though bacterial cells, of size ~1 -2m, are well below the Kolmogoroff microscale of turbulence, it has been reported that the mean cell volume of two strains of E. coli and of two other species of bacteria, increased linearly with impeller speed during continuous cultivation with a concomitant increase in intracellular potassium and sodium ion concentration (Wase and Patel, 1985;Wase and Rattwatte, 1985). Toma et al (1991) also studied the effect of mechanical agitation on two species of bacteria, Brevibactarium flavium and Tricherderma reesii. In each case, they found that under conditions of high agitation intensity during batch culture, both growth and metabolism, were inhibited.…”
Section: A Fluid Mechanical Stress or So Called 'Shear Damage'mentioning
confidence: 99%
See 1 more Smart Citation
“…However, even though bacterial cells, of size ~1 -2m, are well below the Kolmogoroff microscale of turbulence, it has been reported that the mean cell volume of two strains of E. coli and of two other species of bacteria, increased linearly with impeller speed during continuous cultivation with a concomitant increase in intracellular potassium and sodium ion concentration (Wase and Patel, 1985;Wase and Rattwatte, 1985). Toma et al (1991) also studied the effect of mechanical agitation on two species of bacteria, Brevibactarium flavium and Tricherderma reesii. In each case, they found that under conditions of high agitation intensity during batch culture, both growth and metabolism, were inhibited.…”
Section: A Fluid Mechanical Stress or So Called 'Shear Damage'mentioning
confidence: 99%
“…Thus, any experimental protocol for investigating the impact of fluid dynamic stress on cell response should be undertaken under steady state (continuous culture) conditions, including the control of dO 2, if the cause of the change is to be determined conclusively. Therefore in the cases discussed above the results were probably based on poor experimental design and their controversial findings may have been due to the lack of controlled dO 2 (Wase and Patel, 1985;Wase and Rattwatte, 1985) or the use of the constantly changing conditions experienced during batch culture (Toma et al, 1991).…”
Section: A Fluid Mechanical Stress or So Called 'Shear Damage'mentioning
confidence: 99%
“…Hence, these morphological changes may be regarded to be not a simple result of the mechanical deformation of cells, but a reaction to the changes in cultivation conditions. Moreover, the dependence of the synthesis of histamine (which is regarded as a characteristic mark of stress) on the turbulence intensity in a bioreactor was established [52,71,78,79].…”
Section: Figmentioning
confidence: 99%
“…Changes in enzyme activity are also observed in conditions when the morphological changes in cells are not yet visible [52,71,78,[80][81][82][83][84], which means that the deformation of cells as well as the damages and destruction of the cell membrane are a manifestation of the extreme stress, while the inner structures of the cell react to the hydrodynamic stress at much lower values of the turbulence intensity. If the enzyme activity of cells changes, then the amount and content of the metabolism product also must change.…”
Section: Figmentioning
confidence: 99%
“…Our study shows that the viable cells remained constant even cell concentration (in term of cell dry weight) increased. Because during the process, the livings cells undergo stress, which result in change in physiology (decrease of global activity and of viability) and possibly in morphology (appearance of cell damage and lysis) (Toma, et al, 2000). .…”
Section: Effect Of Feeding Sugar Concentrationmentioning
confidence: 99%